(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Injuries to muscles, joints, and bones are some of the most common emergencies you will encounter in the field. They can range from simple and non-life-threatening injuries (such as a broken finger or sprained ankle) to critical and life-threatening injuries (such as a fracture of the femur or spine). Regardless of whether the injury is mild or severe, your ability to provide emergency care efficiently and quickly can prevent further painful and damaging injury and might even keep the patient from suffering permanent disability or death.